Vibration analysis for failure detection in clean water distribution pumps: A case study in an oil and gas training center - Novianto, Hernawan; Sujono, Sujono (Politeknik Negeri Lhokseumawe, 2025)
The Clean Water Distribution Pump plays a crucial role in delivering clean water to consumers. Over time, increased noise levels indicate potential damage to pump components, which, if left unaddressed, can lead to severe failures and costly repairs. One of the analyzes of pump damage is vibration analysis. With vibration analysis, damage to the pump in the form of misalignment, mechanical looseness, bent shaft, bearing damage, worn gears, cavitation can be identified. The purpose of this research is to determine the characteristics of vibrations that occur in the pump, so that we can detect damage and failures that occurs and suggest maintenance action. Vibration analysis is carried out using a vibration analyzer to determine the vibration spectrum that occurs in the axial, radial and tangential directions, then analyzing the type of damage and appropriate maintenance to be carried out. The results showed that this pump indicated: extreme motor free end bearing looseness with a severity score of 99/100, serious motor free end bearing wear with a severity score of 72/100, serious motor drive end bearing looseness with a severity score of 53/100, and moderate motor drive end bearing wear with a severity score of 37/100. and based on the ISO 10816-3 standard, it is recommended that the motor free end bearing be replaced because vibration will cause damage and for the drive end bearing motor it is only recommended to operate for a short time.